The Use of Organic Fertilizer to Enhance Soil Water Availability and Promote the Growth of Tomatoes in Sandy Loam Soils - Abdul Rahman; Danang Widjajanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The use of organic fertilizer has been shown to improve soil structure and promote plant root growth, particularly in critical areas with limited water resources for agricultural activities. This study aimed to evaluate the effect of organic fertilizer application on the soil’s water holding capacity and the growth performance of tomato. The experiment was conducted using a randomized complete blocs design with six treatments, each replicated three times. The treatments included P0 (0 Mg/ha), P1 (5 Mg/ha), P2 (10 Mg/ha), P3 (15 Mg/ha), P4 (20 Mg/ha), and P5 (25 Mg/ha). The findings revealed that organic fertilizer application significantly influenced soil organic carbon levels, bulk density, hydraulic conductivity, and soil water availability. Additionally, the increased soil organic carbon led to noticeable improvements in shoot dry weight, total root length, and root dry weight of tomatoes. This study found that the availability of organic carbon has very strong correlation with tomatoes growth and soil water availability. Keywords: Organic Carbon, Sandy Soils Texture, Soil Structure, Water Retention.